The Impact of Market Relocation on the Income of Traders in Sorong City - Fadhila Fadhila; Hasbiah Hasbiah; Abdul Rahman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the impact of market relocation on traders’ income at Rufei Modern Market, Sorong City. The research employs a quantitative approach using primary data collected from 50 traders who experienced the relocation process. Data were analyzed through descriptive statistics, validity and reliability tests, normality testing, paired sample t-test, and simple linear regression. The results show that market relocation improved the physical quality of the trading environment, including facilities, comfort, security, and spatial organization. However, these improvements were not followed by better economic outcomes. The average daily income of traders decreased from IDR 475,000 before relocation to IDR 398,000 after relocation, indicating a decline of 16.2%. The paired sample t-test confirms that this decrease is statistically significant. Regression analysis reveals that positive perceptions of the new market conditions are associated with better income changes, although the influence remains limited. Furthermore, the impact of relocation varies among traders depending on merchandise type, customer dependency, and adaptability. Overall, market relocation has both structural benefits and economic challenges, indicating the need for supporting policies to ensure traders’ sustainability.